Determination of exercise habits, physical activity level and anxiety level of postmenopausal women during COVID-19 pandemic - Kaygisiz, Beliz Belgen; Topcu, Zehra Guchan; Meric, Aydin; Gozgen, Havva; Coban, Fahriye (Taylor & Francis Inc, 2020)
In this study, researchers aimed to determine exercise habits, physical activity (PA) levels and anxiety levels of postmenopausal women (PMw) during the self-quarantine period of the COVID-19 pandemic. 104 PMw (59.00 +/- 6.61 years old) participated in the study. It was found that PMw who had exercise habits before the pandemic period had higher PA levels, and the women with high anxiety levels during the pandemic had lower PA levels (p < .05). Anxiety levels and PA were negatively associated with each other. Numbers of grandchildren also affected the PA and anxiety levels of the PMw negatively. Women should be encouraged to initiate or maintain PA levels in all circumstances.